FORMATION OF PRIMARY MATHEMATICAL KNOWLEDGE IN CHILDREN AS A CONDITION FOR SUCCESSFUL EDUCATION IN THE NEW UKRAINIAN SCHOOL - Dovgij, Oleg; Bai, Ihor (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the problem of the formation of mathematical competence of students, in particular the issue of the formation of initial mathematical knowledge in children. Mathematical competence is one of the key competences of the schoolchildren. Nowadays, the acquisition of mathematical competence is an indicator of the quality of education at the international level and the country's competitiveness in the field of fundamental sciences and the latest technologies. Therefore, it is necessary to form initial mathematical knowledge at preschool age, and the process formation of mathematical competence by the teachers of the New Ukrainian School (hereinafter, NUS), which are carried out from the first year of a child's education at school. It should be implemented on the principles of partnership, continuity, and perspective. Among the teaching methods, it is appropriate to use those that are based on the interaction of all participants in the educational process, contribute to the high-quality preparation of children for the transition from one level of education to another. It was concluded that the mathematics course in the continuing education system is based on the appropriate content of the Basic component of preschool education and implements the continuity between preschool and primary school in the field of logical-mathematical development, as well as provides perspective in teaching mathematics in the 5th grade. Among the tasks of primary mathematical education is the formation of elementary mathematical ideas and concepts, in particular the following: acquisition of knowledge about set, number, size, shape, space and time; formation of a broad initial orientation in quantitative, spatial and temporal relations of the surrounding reality; formation of skills and abilities in numbers, measurements, calculations; mastering mathematical terminology; development of cognitive interests and abilities, mental development of the child in general. In the New Ukrainian School (NUS), mathematics education acquires new features. Computational, measuring, geometric, algebraic, information-graphic, logical, and communicative are the components of subject-matter mathematical competence of a student of primary education.